Preparation method of laser-assisted titanium alloy ion nitriding wear-resistant coating
Through laser-assisted ion nitriding technology, the "hard shell" structure on the surface of titanium alloy workpieces is eliminated, and nitrogen ion diffusion is promoted, which solves the problem of insufficient thickness of titanium alloy coatings in the prior art, and achieves a thicker and higher quality wear-resistant coating, improving the performance of the material under high load conditions.
Patent Information
- Application Number
- CN202411918203.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-28
AI Technical Summary
The wear-resistant coating prepared by the existing titanium alloy ion nitriding technology is small in thickness and cannot meet the material performance requirements of aerospace and other fields for high load friction conditions.
Laser-assisted ion nitriding method is used to form a wear-resistant coating on the surface of the titanium alloy workpiece, and the "hard shell" structure on the surface of the seepage layer is eliminated by laser remelting, thereby promoting nitrogen ion diversion and improving the coating thickness and quality.
The thickness and quality of the wear-resistant coating are significantly improved, the service time and reliability of titanium alloy workpieces under load friction conditions are improved, and the problem of insufficient coating thickness in the prior art is solved.
Smart Images

Figure CN119710536A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of surface modification, and in particular relates to a method for preparing a laser-assisted titanium alloy ion nitriding wear-resistant coating. Background Art
[0002] Titanium alloy has excellent comprehensive properties, low density, high thermal stability, high specific strength, excellent corrosion resistance, good toughness and weldability. In the field of aerospace, titanium alloy has been widely used because of its light weight, high strength and excellent medium temperature performance. Worldwide, aerospace demand accounts for about 80% of titanium production, which is an important indicator of a country's aerospace industry. The advancement of aircraft is positively correlated with the amount of titanium alloy used. The amount of titanium alloy used in F22 fighter is as high as 41%. Combined with the increase in the proportion of titanium alloy used in new models in recent years, considering the single-machine usage and yield rate, an average of 50 tons of titanium is consumed per aircraft. Most of the key components such as engine compressor blades, aircraft landing gear, turbine discs and turbine blades use titanium alloys. However, during the flight of the aircraft, key structural parts often produce long-term load friction, which leads to material failure, seriously affecting the development of titanium alloys in aerospace and other fields. At present, the tribological behavior of the titanium alloy surface can be effectively improved through surface modification technology.
[0003] As a kind of material surface strengthening technology, titanium alloy ion nitriding technology has the advantages of high activity, fast penetration rate, and easier to reach a deeper penetration layer, which can effectively improve the friction, wear and micro-fatigue performance of the material. The principle of titanium alloy ion nitriding is to generate nitrogen ions through high-pressure ionized nitrogen gas and then bombard the surface of the workpiece. When a certain nitrogen potential and temperature are reached, the nitrogen ions react on the surface of the titanium alloy to form a wear-resistant coating mainly composed of TiN. The penetration layer structure after ion nitriding treatment has good bonding with the matrix, without subsequent processing and penetration layer defect problems, the surface state is complete, and the surface layer is in a compressive stress state. However, the wear-resistant coating prepared by ion nitriding is currently shallow, and the penetration layer thickness is generally 40μm to 70μm, so this technology is currently only used on light-loaded structural parts.
[0004] Research has found that there is a "hard shell layer" structure on the surface of titanium alloy ion nitriding. This is because the nitrogen potential on the workpiece surface gradually increases in the early stage of nitriding. When the nitriding temperature is reached, a "hard shell layer" structure similar to a white bright layer will be generated on the workpiece surface. This hardened layer will prevent nitrogen ions from diffusing into the interior of the workpiece during the subsequent nitriding process, causing the nitriding layer to become thinner, which seriously affects the application of titanium alloy in key aerospace structural parts and other fields. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a method for preparing a wear-resistant coating by laser-assisted ion nitriding of titanium alloy in view of the deficiencies of the above-mentioned prior art. The method adopts a laser-assisted ion nitriding method to prepare a wear-resistant coating on the surface of a titanium alloy workpiece, and utilizes laser remelting to eliminate the "hard shell layer" structure on the surface of the nitrided layer, so that the nitrogen ions can further diffuse into the interior of the workpiece, thereby improving the thickness and quality of the wear-resistant coating, and solving the problem that the thickness of the wear-resistant coating prepared by nitriding on the surface of the titanium alloy is relatively small.
[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a laser-assisted titanium alloy ion nitriding wear-resistant coating, characterized in that the method comprises the following steps:
[0007] Step 1, pre-treatment: using wire cutting to cut the titanium alloy workpiece, and then grinding, cleaning and drying the surface to obtain the treated titanium alloy workpiece;
[0008] Step 2, ion nitriding: Place the titanium alloy workpiece treated in step 1 in a nitriding device, turn on the power and introduce nitrogen and argon, adjust the voltage and gas pressure, and perform ion nitriding on the treated titanium alloy workpiece to form a nitrided layer with a "hard shell layer" structure;
[0009] Step 3, laser remelting: adjusting the composition ratio of nitrogen and argon introduced into the nitriding equipment, turning on the laser generator to laser remelt the nitrided layer containing the "hard shell layer" structure in the titanium alloy workpiece in step 2, and destroying the "hard shell layer" structure;
[0010] Step 4: Ion nitriding and diffusion: adjust the composition ratio of nitrogen and argon introduced into the nitriding equipment, and change the temperature by adjusting the nitriding voltage, and perform ion nitriding and diffusion on the titanium alloy workpiece after laser remelting in step 3 to form a wear-resistant coating with significantly increased nitriding layer thickness.
[0011] The above-mentioned method for preparing a laser-assisted titanium alloy ion nitriding wear-resistant coating is characterized in that the titanium alloy workpiece in step 1 is selected from TA and TC series titanium alloys. Typical grades are TA5, TA16, TA21, TC4, TC6, TC11, and TC21 titanium alloys.
[0012] The above-mentioned method for preparing a laser-assisted titanium alloy ion nitriding wear-resistant coating is characterized in that the volume proportion of nitrogen in the nitrogen and argon introduced in step 2 is 85% to 95%, and the volume proportion of argon is 5% to 15%. The gas pressure after the introduction of nitrogen and argon is 180Pa to 220Pa, the voltage of the ion nitriding is 750V to 850V, the temperature is 820℃ to 880℃, and the insulation time is 4h to 6h.
[0013] The above-mentioned method for preparing a laser-assisted titanium alloy ion nitriding wear-resistant coating is characterized in that in step 3, the volume proportion of nitrogen in the nitrogen and argon gases introduced is adjusted to 5% to 15%, the volume proportion of argon is adjusted to 85% to 95%, and the gas pressure is 180Pa to 220Pa. By adjusting the ratio of the introduced nitrogen and argon gases, a protective atmosphere is provided during the laser remelting stage to avoid the continuous generation of a "hard shell layer" structure on the surface of the titanium alloy workpiece during the laser remelting stage, thereby affecting the laser remelting process.
[0014] The above-mentioned method for preparing a laser-assisted titanium alloy ion nitriding wear-resistant coating is characterized in that the laser power of the laser remelting in step three is 1000W~1400W, the laser spot is a circular spot, the spot diameter is 0.5mm~1mm, the scanning speed is 100mm / min~300mm / min, and the overlap rate is 30%~50%.
[0015] The above-mentioned method for preparing a laser-assisted titanium alloy ion nitriding wear-resistant coating is characterized in that the volume proportion of nitrogen in the nitrogen and argon gases introduced in step four is adjusted to 85% to 95%, the volume proportion of argon is 5% to 15%, and the air pressure is 180Pa to 220Pa; the voltage of the ion nitriding diffusion is 650V to 750V, the temperature is 670℃ to 730℃, and the insulation time is 8h to 12h.
[0016] The above-mentioned method for preparing a laser-assisted titanium alloy ion nitriding wear-resistant coating is characterized in that the mass purity of the nitrogen and argon gases introduced in steps 2 to 4 is not less than 99.99%.
[0017] The above-mentioned method for preparing a laser-assisted titanium alloy ion nitriding wear-resistant coating is characterized in that the thickness of the wear-resistant coating in step four is 100μm to 160μm.
[0018] Compared with the prior art, the present invention has the following advantages:
[0019] 1. The present invention first performs preliminary ion nitriding on the surface of the titanium alloy workpiece, and then destroys and eliminates the "hard shell layer" structure in the nitrided layer by laser remelting, thereby avoiding the obstruction of the structure to the diffusion of nitrogen ions, and then performs ion nitriding diffusion to prepare a thicker wear-resistant coating on the surface of the titanium alloy workpiece, thereby increasing the thickness and quality of the wear-resistant coating and improving the service life and reliability of the titanium alloy workpiece under load friction conditions.
[0020] 2. Compared with the disadvantage of single ion nitriding that the cross-sectional hardness of the infiltrated layer drops sharply under the "hard shell layer" structure, the present invention adopts laser remelting treatment to eliminate the "hard shell layer" structure in the infiltrated layer while combining subsequent ion nitriding diffusion to form the infiltrated layer in stages, so that the interface hardness of the wear-resistant coating presents a continuous step-like change, and a wear-resistant coating with a uniform infiltrated layer is obtained, thereby improving the surface quality of the wear-resistant coating on the surface of the titanium alloy workpiece.
[0021] 3. The present invention performs ion nitriding and diffusion treatment after laser remelting treatment. Through secondary nitriding and low-temperature diffusion, the nitrogen concentration on the surface and inner layer of the titanium alloy workpiece after the laser remelting destroys the "hard shell layer" structure in the diffusion layer presents an obvious gradient, which is conducive to further penetration of nitrogen ions into the interior of the titanium alloy workpiece, and realizes low-temperature nitriding while obtaining a thicker diffusion layer, effectively solving the phase change and workpiece deformation problems caused by single ion nitriding.
[0022] 4. The wear-resistant coating prepared by the present invention has complete crystal structure and is well bonded to the base titanium alloy workpiece, which helps to improve the comprehensive performance of the wear-resistant coating.
[0023] 5. The wear-resistant coating preparation process of the present invention is simple and has high reliability. It is easy to realize mass production of titanium alloy ion nitriding coating and is suitable for popularization and application.
[0024] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a cross-sectional microstructure diagram of the wear-resistant coating prepared on the surface of a TC6 alloy workpiece according to Example 2 of the present invention.
[0026] Figure 2 This is a cross-sectional hardness gradient diagram of the wear-resistant coating prepared on the surface of a TC6 alloy workpiece according to Example 2 of the present invention. DETAILED DESCRIPTION
[0027] Example 1
[0028] This embodiment includes the following steps:
[0029] Step 1, pretreatment: Use wire cutting to obtain a rectangular thin block with a size of 40mm×40mm×20mm in length×width×height from the TC6 titanium alloy workpiece, then use a surface grinder and 240#, 400#, 800#, 1200# metallographic sandpaper to polish the surface to remove the surface oxide layer and scratches, then place it in anhydrous ethanol for ultrasonic cleaning for 20 minutes, rinse it with deionized water and blow it dry with an air gun to obtain the treated TC6 titanium alloy workpiece;
[0030] Step 2, ion nitriding: place the TC6 titanium alloy workpiece treated in step 1 in a nitriding device, turn on the power and introduce nitrogen and argon, adjust the voltage and air pressure, and perform ion nitriding on the treated TC6 titanium alloy workpiece to form a nitrided layer containing a "hard shell layer" structure; the volume proportion of nitrogen in the nitrogen and argon introduced is 85%, the volume proportion of argon is 15%, the mass purity of nitrogen and argon is not less than 99.99%, the air pressure after introducing nitrogen and argon is 180Pa, the voltage of the ion nitriding is 750V, the temperature is 820°C, and the insulation time is 4h;
[0031] Step 3, laser remelting: adjust the composition ratio of nitrogen and argon introduced into the nitriding equipment, turn on the laser generator to laser remelt the nitrided layer containing the "hard shell layer" structure in the TC6 titanium alloy workpiece in step 2, and destroy the "hard shell layer" structure; the volume proportion of nitrogen in the nitrogen and argon introduced is adjusted to be 15%, and the volume proportion of argon is 85%, the mass purity of nitrogen and argon is not less than 99.99%, and the air pressure is 180Pa; the laser power of the laser remelting is 1000W, the laser spot is a circular spot, the spot diameter is 0.5mm, the scanning speed is 100mm / min, and the overlap rate is 30%;
[0032] Step 4, ion nitriding and diffusion: adjust the composition ratio of nitrogen and argon introduced into the nitriding equipment, and change the temperature by adjusting the nitriding voltage, and perform ion nitriding and diffusion on the TC6 titanium alloy workpiece after laser remelting in step 3 to form a wear-resistant coating with significantly improved nitriding layer thickness; the volume proportion of nitrogen in the nitrogen and argon introduced is adjusted to be 85%, and the volume proportion of argon is 15%, the mass purity of nitrogen and argon is not less than 99.99%, and the air pressure is 180Pa; the voltage of the ion nitriding and diffusion is 650V, the temperature is 670℃, and the insulation time is 8h.
[0033] After testing, the wear-resistant coating without a "hard shell layer" structure prepared on the surface of the TC6 titanium alloy workpiece in this embodiment has a thickness of 100 μm and a surface hardness of 880 HV 0.1 The surface is smooth and free of impurities, and the workpiece is basically free of deformation.
[0034] The TC6 titanium alloy workpiece of the present embodiment may also be replaced by TA and TC series titanium alloys other than TC6 titanium alloy, such as TA5, TA16, TA21, TC4, TC11, and TC21 titanium alloys.
[0035] Example 2
[0036] This embodiment includes the following steps:
[0037] Step 1, pretreatment: Use wire cutting to obtain a rectangular thin block with a size of 40mm×40mm×20mm in length×width×height from the TC6 titanium alloy workpiece, then use a surface grinder and 240#, 400#, 800#, 1200# metallographic sandpaper to polish the surface to remove the surface oxide layer and scratches, then place it in anhydrous ethanol for ultrasonic cleaning for 20 minutes, rinse it with deionized water and blow it dry with an air gun to obtain the treated TC6 titanium alloy workpiece;
[0038] Step 2, ion nitriding: place the TC6 titanium alloy workpiece treated in step 1 in a nitriding device, turn on the power and introduce nitrogen and argon, adjust the voltage and air pressure, and perform ion nitriding on the treated TC6 titanium alloy workpiece to form a nitrided layer containing a "hard shell layer" structure; the volume proportion of nitrogen in the nitrogen and argon introduced is 90%, the volume proportion of argon is 10%, the mass purity of nitrogen and argon is not less than 99.99%, the air pressure after introducing nitrogen and argon is 200Pa, the voltage of the ion nitriding is 800V, the temperature is 850°C, and the insulation time is 5h;
[0039] Step 3, laser remelting: adjust the composition ratio of nitrogen and argon introduced into the nitriding equipment, turn on the laser generator to laser remelt the nitrided layer containing the "hard shell layer" structure in the TC6 titanium alloy workpiece in step 2, and destroy the "hard shell layer" structure; the volume proportion of nitrogen in the nitrogen and argon introduced is adjusted to be 10%, and the volume proportion of argon is 90%, the mass purity of nitrogen and argon is not less than 99.99%, and the air pressure is 200Pa; the laser power of the laser remelting is 1200W, the laser spot is a circular spot, the spot diameter is 0.8mm, the scanning speed is 200mm / min, and the overlap rate is 40%;
[0040] Step 4, ion nitriding and diffusion: adjust the composition ratio of nitrogen and argon introduced into the nitriding equipment, and change the temperature by adjusting the nitriding voltage, and perform ion nitriding and diffusion on the TC6 titanium alloy workpiece after laser remelting in step 3 to form a wear-resistant coating with significantly improved nitriding layer thickness; the volume proportion of nitrogen in the nitrogen and argon introduced is adjusted to be 90%, and the volume proportion of argon is 10%, the mass purity of nitrogen and argon is not less than 99.99%, and the air pressure is 200Pa; the voltage of the ion nitriding and diffusion is 700V, the temperature is 700℃, and the insulation time is 10h.
[0041] After testing, the wear-resistant coating without a "hard shell layer" structure prepared on the surface of the TC6 titanium alloy workpiece in this embodiment has a thickness of 150 μm and a surface hardness of 960 HV 0.1 The surface is smooth and free of impurities, and the workpiece is basically free of deformation.
[0042] Figure 1This is a cross-sectional microstructure of the wear-resistant coating prepared on the surface of the TC6 alloy workpiece in this embodiment. Figure 1 It can be seen that the main structure of the wear-resistant coating is round equiaxed crystals, doped with a small amount of dendrites.
[0043] Figure 2 This is the cross-sectional hardness gradient diagram of the wear-resistant coating prepared on the surface of the TC6 alloy workpiece in this embodiment, from Figure 2 It can be seen that when the hardness is 50 HV higher than the substrate as the baseline, the thickness of the wear-resistant coating is about 150 μm.
[0044] Example 3
[0045] This embodiment includes the following steps:
[0046] Step 1, pretreatment: Use wire cutting to obtain a rectangular thin block with a size of 40mm×40mm×20mm in length×width×height from the TC6 titanium alloy workpiece, then use a surface grinder and 240#, 400#, 800#, 1200# metallographic sandpaper to polish the surface to remove the surface oxide layer and scratches, then place it in anhydrous ethanol for ultrasonic cleaning for 20 minutes, rinse it with deionized water and blow it dry with an air gun to obtain the treated TC6 titanium alloy workpiece;
[0047] Step 2, ion nitriding: place the TC6 titanium alloy workpiece treated in step 1 in a nitriding device, turn on the power and introduce nitrogen and argon, adjust the voltage and air pressure, and perform ion nitriding on the treated TC6 titanium alloy workpiece to form a nitrided layer containing a "hard shell layer" structure; the volume proportion of nitrogen in the nitrogen and argon introduced is 95%, the volume proportion of argon is 5%, the mass purity of nitrogen and argon is not less than 99.99%, the air pressure after introducing nitrogen and argon is 220Pa, the voltage of the ion nitriding is 850V, the temperature is 880℃, and the insulation time is 6h;
[0048] Step 3, laser remelting: adjust the composition ratio of nitrogen and argon introduced into the nitriding equipment, turn on the laser generator to laser remelt the nitrided layer containing the "hard shell layer" structure in the TC6 titanium alloy workpiece in step 2, and destroy the "hard shell layer" structure; the volume proportion of nitrogen in the nitrogen and argon introduced is adjusted to be 5%, and the volume proportion of argon is 95%, the mass purity of nitrogen and argon is not less than 99.99%, and the gas pressure is 220Pa; the laser power of the laser remelting is 1400W, the laser spot is a circular spot, the spot diameter is 1mm, the scanning speed is 300mm / min, and the overlap rate is 50%;
[0049] Step 4, ion nitriding and diffusion: adjust the composition ratio of nitrogen and argon introduced into the nitriding equipment, and change the temperature by adjusting the nitriding voltage, and perform ion nitriding and diffusion on the TC6 titanium alloy workpiece after laser remelting in step 3 to form a wear-resistant coating with significantly improved nitriding layer thickness; the volume proportion of nitrogen in the nitrogen and argon introduced is adjusted to be 95%, and the volume proportion of argon is 5%, the mass purity of nitrogen and argon is not less than 99.99%, and the air pressure is 220Pa; the voltage of the ion nitriding and diffusion is 750V, the temperature is 730℃, and the insulation time is 12h.
[0050] After testing, the wear-resistant coating without a "hard shell layer" structure prepared on the surface of the TC6 titanium alloy workpiece in this embodiment has a thickness of 160 μm and a surface hardness of 980 HV 0.1 The surface is smooth and free of impurities, and the workpiece is basically free of deformation.
[0051] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a laser-assisted titanium alloy ion nitriding wear-resistant coating, characterized in that: The method comprises the following steps: Step 1, pre-treatment: using wire cutting to cut the titanium alloy workpiece, and then grinding, cleaning and drying the surface to obtain the treated titanium alloy workpiece; Step 2, ion nitriding: Place the titanium alloy workpiece treated in step 1 in the nitriding equipment, turn on the power and introduce nitrogen and argon, adjust the voltage and gas pressure, and perform ion nitriding on the treated titanium alloy workpiece to form a nitrided layer with a "hard shell layer" structure; Step 3, laser remelting: adjust the composition ratio of nitrogen and argon introduced into the nitriding equipment, turn on the laser generator to laser remelt the nitrided layer containing the "hard shell layer" structure in the titanium alloy workpiece in step 2, and destroy the "hard shell layer" structure; Step 4: Ion nitriding and diffusion: adjust the composition ratio of nitrogen and argon introduced into the nitriding equipment, and change the temperature by adjusting the nitriding voltage, and perform ion nitriding and diffusion on the titanium alloy workpiece after laser remelting in step 3 to form a wear-resistant coating with significantly increased nitriding layer thickness.
2. The method for preparing a laser-assisted titanium alloy ion nitriding wear-resistant coating according to claim 1, characterized in that: The titanium alloy workpiece in step 1 is selected from TA and TC series titanium alloys.
3. The method for preparing a laser-assisted titanium alloy ion nitriding wear-resistant coating according to claim 1, characterized in that: The volume proportion of nitrogen in the nitrogen and argon introduced in step 2 is 85% to 95%, and the volume proportion of argon is 5% to 15%. The gas pressure after the introduction of nitrogen and argon is 180Pa to 220Pa, the voltage of the ion nitriding is 750V to 850V, the temperature is 820℃ to 880℃, and the insulation time is 4h to 6h.
4. The method for preparing a laser-assisted titanium alloy ion nitriding wear-resistant coating according to claim 1, characterized in that: In step 3, the volume proportion of nitrogen in the nitrogen and argon gases introduced is adjusted to be 5% to 15%, the volume proportion of argon is adjusted to be 85% to 95%, and the gas pressure is adjusted to be 180Pa to 220Pa.
5. The method for preparing a laser-assisted titanium alloy ion nitriding wear-resistant coating according to claim 1, characterized in that: The laser power of the laser remelting in step three is 1000W to 1400W, the laser spot is a circular spot, the spot diameter is 0.5mm to 1mm, the scanning speed is 100mm / min to 300mm / min, and the overlap rate is 30% to 50%.
6. The method for preparing a laser-assisted titanium alloy ion nitriding wear-resistant coating according to claim 1, characterized in that: In step 4, the volume proportion of nitrogen in the nitrogen and argon gases introduced is adjusted to 85% to 95%, the volume proportion of argon is 5% to 15%, and the gas pressure is 180Pa to 220Pa; the voltage of the ion nitriding diffusion is 650V to 750V, the temperature is 670℃ to 730℃, and the insulation time is 8h to 12h.
7. The method for preparing a laser-assisted titanium alloy ion nitriding wear-resistant coating according to claim 1, characterized in that: The mass purity of the nitrogen and argon introduced in steps 2 to 4 is not less than 99.99%.
8. The method for preparing a laser-assisted titanium alloy ion nitriding wear-resistant coating according to claim 1, characterized in that: The thickness of the wear-resistant coating in step 4 is 100 μm to 160 μm.
Citation Information
Cited By
TC4 titanium alloy surface strengthening layer based on ion implantation and ion nitriding treatment as well as treatment method and application of TC4 titanium alloy surface strengthening layer
CN121046773A
Titanium alloy surface gradient hardening layer and titanium alloy surface gradient hardening method
CN122406145A